Developing Data Elements for Research Information System in Health; a Starting Point for Systems Integration - NR Ghorbani; M Ahmadi; F Sadoughi; M Ghanei (Tehran University of Medical Sciences, 2012)
Background: This study defines necessary data elements required for the research information system in the domain of health, and its level of accountability to national health research indicators from the experts' perspective is being explored.Methods: This qualitative study was conducted based on comparative approach using the focus group method. Data were collected through 6 semi-structured group discussions held at the Undersecretary for Research and Technology, Ministry of Health and Medical Education, Tehran, Iran. For this study, 48 researchers were selected for the group discussions. All interviews and group discussions were recorded and transcribed. The Data analysis was performed simultaneously using Strauss and Corbin method.Results: Based on content analysis, the necessary data elements identified for the National Health Research Information System designed for all databases were the following: organizations, researchers, journals, articles, research projects and dissertations. Also, extracted from the focus group discussion were three main themes regarding data elements of these databases for the National Health Research Information System: 1) essential elements for each database 2) the system's data elements accountability to the national indicators in the domain of health research and 3) recommendations in the direction of optimizing the data.Conclusions: The results obtained from this study can serve as a valuable source in designing research information system in the domain of health within the country and in the region as well